Evolution of magnetic properties in iron-based superconductor Eu-doped CaFe2As2 - Shrestha, K.; Deng, L. Z.; Lv, B.; Chu, C. W. (Frontiers in Electronic Materials, 2022)
This work presents the evolution of magnetic properties of Eu-doped Ca1−xFe2As2 (0 ≤ x ≤ 1, ECFA) samples. Unlike the resistivity data, that for magnetic susceptibility χ (T) does not show any clear evidence of the spin density wave (SDW) transition. When the Curie-Weiss contribution is subtracted, a weak anomaly appears at a temperature close to the SDW transition temperature determined from the resistivity data. To understand the magnetic orders arising from Fe-moments and Eu2+ spins order, we have studied the doping dependence of TSDW and TN . It is found that TSDW increases almost linearly with increasing x and remains nearly unchanged above x ∼ 0.4, whereas TN first appears at x ∼ 0.4 and varies almost linearly with further increasing x. These observations suggest that magnetic orders due to two sublattices are coupled to each other. The results discussed here are helpful for understanding the magnetic properties of ECFA and other iron-based superconductors.